2016
DOI: 10.1111/epi.13619
|View full text |Cite
|
Sign up to set email alerts
|

Disclose or not? Effect of impression management tactics on hireability of persons with epilepsy

Abstract: SUMMARYObjective: The purpose of this study is to determine the effect of assertive impression management (IM) tactics, such as personal storytelling and self-promotion, on job interview outcomes of people with epilepsy. Specifically, the effect of IM on interviewers' subjective impressions and evaluation of hireability of job candidates with epilepsy were examined. Methods: Ninety-nine master's level graduate students majoring in business or human resources were randomly assigned to three experimental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This aim is actuated and influenced by three main observations from the extant literature. Firstly, there is a growing body of international literature calling for focus on understanding impression management within organisational studies (Howle et al, 2014;Kacmar & Carlson, 1999;Patel et al, 2011;Schlenker, 1980;Sung et al, 2017). Secondly, calls exist with the South African IOP context to be expansive in understanding the concept of impression management (Mtshelwane et al, 2016).…”
Section: Research Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…This aim is actuated and influenced by three main observations from the extant literature. Firstly, there is a growing body of international literature calling for focus on understanding impression management within organisational studies (Howle et al, 2014;Kacmar & Carlson, 1999;Patel et al, 2011;Schlenker, 1980;Sung et al, 2017). Secondly, calls exist with the South African IOP context to be expansive in understanding the concept of impression management (Mtshelwane et al, 2016).…”
Section: Research Objectivesmentioning
confidence: 99%
“…The AT posits that individuals make attributions a basis of interaction and that may often result in bias (Spitzberg & Manusov, 2014). Interviews by nature can provide an opportunity through which this bias can happen (Sung et al, 2017), as they form a basis through which interviewees can express themselves to interview panels (Caruth, Caruth & Pane, 2009). Thus, the AT seeks to provide a plausible explanation of events from the lens of the individual (Merkl-Davies, Brennan & Mcleay, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between IM tactics and interview outcomes has been a focal topic in IM research. However, previous studies have yielded inconsistent results regarding the effectiveness of assertive and defensive tactics (e.g., Chen, Huang, Huang, & Liu, ; Peeters & Lievens, ; Sung et al ., ; Van Iddekinge, McFarland, & Raymark, ), highlighting the importance of addressing the boundary conditions under which the association between IM tactics and interview outcomes is investigated. Existing research has supported the moderating role of various factors, including the applicants’ gender (Wosinska, Dabul, Whetstone‐Dion, & Cialdini, ), the interview structure and length, and the job type (Ruben, Hall, & Schmid Mast, ; Tsai, Chen, & Chiu, ).…”
Section: Introductionmentioning
confidence: 99%
“…During interviews, nearly all job applicants engage in impression management (IM) to impress recruiters and obtain their goal of employment (Bye et al, 2011;Levashina & Campion, 2007). Although many studies have demonstrated a positive association between IM tactics and interview ratings (e.g., Peck & Levashina, 2017;Proost, Schreurs, De Witte, & Derous, 2010;Sung, Lin, Connor, & Chan, 2017), the findings on the effects of IM tactics are not consistent (Chen, Yang, & Lin, 2010). To address these inconsistencies, the boundary conditions of the effects of IM tactics have been highlighted.…”
mentioning
confidence: 99%